Role of atrial septostomy in the treatment of children with pulmonary arterial hypertension. Issue 7 (8th November 2005) - Micheletti, A; Hislop, A A; Lammers, A; Bonhoeffer, P; Derrick, G; Rees, P; Haworth, S G
Abstract : Objectives: To assess in retrospect the safety and effectiveness of atrial septostomy in children with severe pulmonary arterial hypertension without an intracardiac communication. Methods: 20 patients were reviewed retrospectively, 19 with idiopathic pulmonary arterial hypertension. The mean age at septostomy was 8.4 years (range 3 months to 17 years). Graded balloon septostomy alone was carried out in eight patients, a blade septostomy was done in two, a blade septostomy plus graded balloon septostomy was done in three, and a fenestrated device was inserted in seven. Results: There were no fatalities. Four children suffered complications during the procedure. None had further syncope and all improved symptomatically with a significant (p < 0.01) decrease in World Health Organization functional class (mean shift −0.6) and a significant improvement in the semiquantitative echocardiographic assessment of right ventricular function (p < 0.03). The mean oxygen saturation decreased by 7.8 percentage points. The atrial communication closed in two children, necessitating a repeat procedure. After a mean follow up of 2.1 years (range one month to 6.7 years), 18 of 20 children are still alive. Conclusion: Atrial septostomy improved symptoms and quality of life in a group of children deteriorating with severe pulmonary arterial hypertension. This procedure is to be recommended for severely symptomatic children, before they become critically ill. Fenestrated devices may help ensure indefinite patency of the atrial communication.